2018
DOI: 10.13052/jmm1550-4646.1415
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Global and RegionalMainstreaminess for Personalized MusicRecommender Systems

Abstract: The music mainstreaminess of a listener reflects how strong a person's listening preferences correspond to those of the larger population. Considering that music mainstream may be defined from different perspectives, we show country-specific differences and study how taking into account music mainstreaminess influences the quality of music recommendations. In this paper, we first propose 11 novel mainstreaminess measures characterizing music listeners, considering both a global and a countryspecific basis for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…e traditional content-based recommendation algorithm first gets the items that have interacted with users and then gets the user's preference model through similar user's active behaviors such as users' likes or ratings of items. User feedback on the project includes implicit and explicit ones [24,25]. e former is the log of users' marks when using the system, which reflects users' interest in the project, such as browsing the lyrics of songs and the number of times the songs are played repeatedly.…”
Section: Application Of Deep Learning In Recommendation Systemmentioning
confidence: 99%
“…e traditional content-based recommendation algorithm first gets the items that have interacted with users and then gets the user's preference model through similar user's active behaviors such as users' likes or ratings of items. User feedback on the project includes implicit and explicit ones [24,25]. e former is the log of users' marks when using the system, which reflects users' interest in the project, such as browsing the lyrics of songs and the number of times the songs are played repeatedly.…”
Section: Application Of Deep Learning In Recommendation Systemmentioning
confidence: 99%
“…In this chapter we focus on the bias towards the so-called mainstream users. A mainstream user often prefers items liked by many people and also reacts negatively to items widely disliked by others [106]. Contrary to this, non-mainstream users typically show interest on rarely-visited items or have an opposite attitude towards widely accepted or rejected items.…”
Section: Introductionmentioning
confidence: 95%
“…They observed that, although only taking a small proportion of users, kids and adolescents have significantly different preferences from other age groups in terms of music genres, and the recommendation performance on these two groups is also distinctive among all users. To repair the unfairness caused by the mainstream bias, several recent works aim at identifying non-mainstream music listeners and using the power of cultural aspects [106,89] and human memories [61] to better profile these underrepresented users in recommender systems. Despite the reported progress, existing methods to alleviate the mainstream bias usually rely on their specific definitions of mainstreamness, which may limit the findings.…”
Section: Biases In Recommender Systemsmentioning
confidence: 99%